2016
DOI: 10.1002/cbic.201600245
|View full text |Cite
|
Sign up to set email alerts
|

6‐Substituted 2‐Aminopurine‐2′‐deoxyribonucleoside 5′‐Triphosphates that Trace Cytosine Methylation

Abstract: Gene expression is extensively regulated by the occurrence and distribution of the epigenetic marker 2′‐deoxy 5‐methylcytosine (5mC) in genomic DNA. Because of its effects on tumorigenesis there is an important link to human health. In addition, detection of 5mC can serve as an outstanding biomarker for diagnostics as well as for disease therapy. Our previous studies have already shown that, by processing O 6‐alkylated 2′‐deoxyguanosine triphosphate (dGTP) analogues, DNA polymerases are able to sense the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In addition, we could ensure selectivity for this incorporation opposite C in comparison to the other nucleobases T, A and G. Taken together, by employing a systematic approach to mutate KOD exo- DNA polymerase and subsequent screening, we identified mutants at one site of KOD exo- DNA polymerase that are capable to discriminate between C and 5mC. Interestingly, the herein developed system keeps the selectivity for incorporation according to the Watson–Crick rule which is in stark contrast to earlier approaches that exploit modified nucleotides (35,41). A multiple sequence alignment of several family-B DNA polymerases (Supplementary Figure S7) shows that the glycine identified in this study is conserved among several family B DNA polymerases.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, we could ensure selectivity for this incorporation opposite C in comparison to the other nucleobases T, A and G. Taken together, by employing a systematic approach to mutate KOD exo- DNA polymerase and subsequent screening, we identified mutants at one site of KOD exo- DNA polymerase that are capable to discriminate between C and 5mC. Interestingly, the herein developed system keeps the selectivity for incorporation according to the Watson–Crick rule which is in stark contrast to earlier approaches that exploit modified nucleotides (35,41). A multiple sequence alignment of several family-B DNA polymerases (Supplementary Figure S7) shows that the glycine identified in this study is conserved among several family B DNA polymerases.…”
Section: Discussionmentioning
confidence: 88%
“…We have engineered a variant of Thermococcus kodakaraensis (KOD) exo- DNA polymerase that enables the direct discrimination between C and 5mC at single sites when primer extension is performed from mismatched primer termini while matched primer template complexes failed to show significant discrimination (40). Furthermore, we explored the potential of modified nucleotides to be employed in site specific 5mC detection (35,41). We found that O 6 -alkylated dGTP-analogues are processed opposite C and 5mC with different efficiencies by KOD exo- DNA polymerase.…”
Section: Introductionmentioning
confidence: 99%
“…bisulfite sequencing of m 5 C, or SHAPE-MaP 52 ) or unnatural bases (e.g. insertion of artificial nucleotides opposite m 5 C or O 6 -BnG 5356 ) opposite modified nucleotides or arrest of the polymerase activity, if it cannot efficiently insert a base opposite the modification site (e.g. adenosine methylation by DMS or older versions of SHAPE probing 57, 58 ).…”
Section: Introductionmentioning
confidence: 99%
“…Category 3 consists of primer extension assays utilizing either incorporation of natural (e.g., bisulfite sequencing of m 5 C, or SHAPE-MaP) or unnatural bases (e.g., insertion of artificial nucleotides opposite m 5 C or O 6 -BnG ) opposite modified nucleotides or arrest of the polymerase activity, if it cannot efficiently insert a base opposite the modification site (e.g., adenosine methylation by DMS or older versions of SHAPE probing , ). Currently, there are no known artificial bases that can be inserted opposite OG or the hydantoin lesions with the required specificity to map exclusively these sites .…”
mentioning
confidence: 99%
“…This fidelity data foreshadows an important limitation in enzymatic XNA synthesis that will likely need to be addressed as the field moves forward. On the other hand, the promiscuous behavior of polymerases has been leveraged to read and record the presence of epigenetic DNA and RNA modifications via misincorporation "signatures" at the modifications [162][163][164][165][166][167][168][169][170]. In addition, the first instance of direct sequencing of an XNA was recently reported; FANA was sequenced using nanopore technology, albeit with relatively short read lengths [171].…”
Section: Analysis Of Xnas and Xna Polymerasesmentioning
confidence: 99%